Method of evaluating and determining molybdenum disulfide coating of titanium and titanium alloy wire

CN117554279BActive Publication Date: 2026-10-16GUOHE GENERAL TESTING EVALUATION & CERTIFICATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311454960.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-03
Publication Date
2026-10-16
Estimated Expiration
2043-11-03

AI Technical Summary

Technical Problem

[0005]为了克服现有技术的不足,本发明的目的是提供一种评价紧固件用钛及钛合金丝材的二硫化钼涂层的耐磨性的试验方法,解决不能试验评价紧固件用钛及钛合金丝材的二硫化钼涂层在热镦(或温镦)过程中二硫化钼涂层耐磨性的问题

Benefits of technology

从结果可以看出,本发明用于紧固件用钛及钛合金丝材的二硫化钼涂层的耐磨性评价方法不仅给出了样品制备的要求和测试方法,而且还给出了评价耐磨性的方法,得到的数据均匀性好,准确度高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117554279B_ABST
    Figure CN117554279B_ABST
Patent Text Reader

Abstract

A method for evaluating and determining the wear resistance of a molybdenum disulfide coating of titanium and titanium alloy wire, comprising the steps of: 1) preparing a pair of abrasion counterparts and fixing the pair of abrasion counterparts; 2) processing a molybdenum disulfide coating sample and fixing the sample; 3) setting the motion form of the friction and wear test to linear motion and setting the experimental parameters: load, speed, stroke and temperature on the software of the friction and wear testing machine; 4) moving the molybdenum disulfide coating sample, so that the fastener coated with the molybdenum disulfide coating titanium and titanium alloy wire is located above the fixed pair of abrasion counterparts; 5) setting the load to make the pair of abrasion counterparts contact the molybdenum disulfide coating sample and keep for more than 1s; 6) clicking the start test button of the friction and wear testing machine, and after the experiment is finished, obtaining the corresponding data of the friction coefficient and time; when the friction coefficient is <0.2 or the maximum friction coefficient is greater than the average value of the friction coefficient in the last 1% to 95% time period, the molybdenum disulfide coating of the fastener titanium and titanium alloy wire has wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of analytical testing, specifically relating to a method for evaluating and determining the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires. Background Technology

[0002] Titanium and titanium alloys for fasteners are widely used in the manufacture of aerospace titanium alloy fasteners due to their high specific strength, corrosion resistance, and excellent fatigue properties. To ensure stable performance of titanium and titanium alloy wires during fastener forming, a molybdenum disulfide coating is typically applied to their surface. This molybdenum disulfide coating is then removed after the fasteners are hot-forged (or warm-forged). To ensure better lubrication and easier removal of the molybdenum disulfide coating later, its wear resistance needs to be tested.

[0003] Currently, there are some standards and specifications for determining the wear resistance of materials. However, for evaluating the wear resistance of complex materials, there is no mature testing method yet. In actual friction analysis, flat plates made of the same material are often used as a substitute. The wear resistance measured by the substitution method often ignores the influence of the sample geometry on the wear resistance, thus affecting the accuracy of the contact analysis results.

[0004] Current methods for evaluating molybdenum disulfide coatings involve coating a layer of molybdenum disulfide onto a smooth titanium alloy substrate, then contacting the coating with a sphere or planar sample and subjecting it to rotational or reciprocating motion under a specific vertical load and speed. The coefficient of friction (cof) is then calculated as (friction force / load). However, this evaluation method cannot fully simulate the wear resistance of titanium and titanium alloys during the extrusion molding process. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the purpose of this invention is to provide a test method for evaluating the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires for fasteners, and to solve the problem that the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires for fasteners cannot be tested and evaluated during hot upsetting (or warm upsetting).

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for evaluating and determining the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires, comprising the following steps: (1) Preparation of grinding pairs: Select the corresponding material according to the material of the extrusion molding die, process it to obtain blocks with regular size, and ensure that the surface is clean and free of defects or obvious scratches; (2) Fixing the grinding pair: Fix the grinding pair prepared in step 1) on the lower sample fixture of the friction and wear testing machine, and ensure that it cannot move; (3) Processing molybdenum disulfide coated samples: Cut the fasteners coated with molybdenum disulfide into cylinders with a length of 3~50mm using titanium and titanium alloy wire; (4) Fixing the molybdenum disulfide coating sample: fix the sample from step 3 laterally on the upper clamp of the friction and wear tester, with the length direction being the contact direction; (5) Set the motion mode of the friction and wear test to linear motion; (6) Set the experimental parameters on the software of the friction and wear testing machine: load, speed, stroke and temperature; (7) Move the upper clamp of the sample with molybdenum disulfide coating downward so that the fastener with molybdenum disulfide coating is positioned above the grinding pair fixed in step 2). (8) Set a load so that the grinding pair is in contact with the molybdenum disulfide coated sample and maintains the contact for more than 1 second; (9) Click the start test button on the friction and wear testing machine, wait for the experiment to end, and obtain the corresponding data of friction coefficient and time; (10) When the coefficient of friction is greater than or equal to 0.2, the molybdenum disulfide coating of titanium and titanium alloy wire for fasteners fails and does not have wear resistance; when the coefficient of friction is less than 0.2, the molybdenum disulfide coating of titanium and titanium alloy wire for fasteners does not fail and has wear resistance. (11) When the time point of the maximum friction coefficient is within the first 5% of the overall time period and the maximum friction coefficient is <0.2, the molybdenum disulfide coating of titanium and titanium alloy wire for fasteners has wear resistance. (12) When the maximum coefficient of friction is greater than the average value of the coefficient of friction in the last 1% to 95% of the time period, the molybdenum disulfide coating of titanium and titanium alloy wire for fasteners has wear resistance.

[0007] Preferably, the linear friction and wear test can be repeated 1 to 30 times at the same location.

[0008] In this invention, the friction coefficient is characterized in that: the average friction coefficient of the first linear friction and wear test is less than or equal to the average friction coefficient of other repeated tests, and the molybdenum disulfide coating of the titanium and titanium alloy wire used for fasteners has wear resistance.

[0009] Preferably, the friction coefficient is characterized in that: the maximum friction coefficient of the first linear friction and wear test is greater than or equal to the maximum friction coefficient of other repeated tests, and the molybdenum disulfide coating of the titanium and titanium alloy wire used for fasteners has wear resistance.

[0010] Preferably, the material of the grinding pair is cemented carbide or high-temperature alloy, the surface roughness is Ra=0.02~0.5μm, the grinding pair is a disc or a cuboid, the size of the disc-shaped grinding pair is φ(10~200)mm×(3~20)mm, and the size of the cuboid-shaped grinding pair is (10~200)mm×(10-60)mm×(3~20)mm.

[0011] Preferably, the diameter of the titanium and titanium alloy wire used for the fastener is 2-8 mm and the length-to-diameter ratio is 1-5.

[0012] Preferably, the molybdenum disulfide coating thickness of the titanium and titanium alloy wire used for the fastener is 5-20 μm.

[0013] Preferably, the parameters for the linear friction and wear test are set as follows: load range of 50N-1000N, stroke of 5mm-30mm, speed of 5mm / min-50mm / min, and temperature range of room temperature to 800℃.

[0014] Preferably, steps 1) and 2) can be interchanged with steps 3) and 4).

[0015] Preferably, the coefficient of friction is less than or equal to 0.18.

[0016] Preferably, the grinding pair is a disc or a cuboid. The size of the disc-shaped grinding pair is φ (10~200) mm × (3~20) mm, and the size of the cuboid-shaped grinding pair is (10~200) mm × (10-60) mm × (3~20) mm.

[0017] The technical effects achieved by this invention are as follows: The results show that the method for evaluating the wear resistance of molybdenum disulfide coatings for titanium and titanium alloy wires for fasteners not only provides the requirements for sample preparation and testing methods, but also provides a method for evaluating wear resistance. The obtained data has good uniformity and high accuracy. Attached Figure Description

[0018] Figure 1 To obtain the friction coefficient data 10 times, and to generate a graph of the friction coefficient.

[0019] Figure 2 To obtain friction coefficient data and a graph of friction coefficient after the experiment.

[0020] Figure 3 To serve as a comparative example, friction coefficient data and a graph of the friction coefficient were obtained. Detailed Implementation

[0021] The technical solution of this disclosure will be described in detail below with specific embodiments. In the following embodiments, all materials used are domestically produced goods, and all equipment used is commonly used in the art.

[0022] Example 1: Abrasion resistance test of molybdenum disulfide coating 1 A TC4 titanium alloy wire with a diameter of 8 mm and a coating thickness of 9.5 μm coated with molybdenum disulfide was used to test the wear resistance of the molybdenum disulfide coating using the following method.

[0023] (1) Select cemented carbide YG20 as the grinding pair. The dimensions after machining are 50mm×20mm×10mm, and the surface roughness Ra=0.05μm. Clean the surface of the grinding pair with acetone and dry it. (2) Cut the TC4 titanium alloy wire with a diameter of 8 mm coated with molybdenum disulfide into cylindrical specimens with a length of 10 mm. (3) Mount the grinding pair on the lower clamp of the friction and wear testing machine, fix the cylindrical sample from step (2) laterally on the upper clamp of the friction and wear testing machine, and move the position of the grinding pair so that the upper clamp is below the grinding pair. (4) Move the lower clamp downwards so that the TC4 titanium alloy wire coated with molybdenum disulfide comes into contact with the YG20 cemented carbide grinding pair. The contact time is 15s when the load is 500N. (5) Set the motion mode to linear motion, the load to 500N, the speed to 10mm / min, and the stroke to 10mm, and start the experiment; (6) After the experiment, the linear friction and wear test was repeated 9 times; (7) Read the friction coefficient data 10 times respectively. The friction coefficients are shown in Table 1 and Figure 1 As shown.

[0024] (8) The friction coefficient is <0.18, the maximum friction coefficient is > the average value of the friction coefficient from 6s to 60s, and the molybdenum disulfide coating of TC4 titanium alloy wire with a diameter of 8mm is wear-resistant.

[0025] Table 1 shows the friction coefficient data from 10 readings. like Figure 1 As shown, the friction coefficient data were read 10 times, with the maximum friction coefficient ranging from 0.161 to 0.148; the average friction coefficient from 6 to 60 seconds was 0.139 to 0.154.

[0026] Example 2: Abrasion resistance test of molybdenum disulfide coating 2 A TC6 titanium alloy wire with a diameter of 6 mm and a molybdenum disulfide coating and a film thickness of 11.2 μm was used to test the wear resistance of the molybdenum disulfide coating using this method.

[0027] (9) Select cemented carbide YG20 as the grinding pair. The dimensions after machining are 50mm×20mm×10mm, and the surface roughness Ra=0.1μm. Clean the surface of the grinding pair with acetone and dry it. (10) Cut a TC6 titanium alloy wire with a diameter of 6 mm coated with molybdenum disulfide into a cylindrical sample with a length of 12 mm. (11) Mount the grinding pair on the lower clamp of the friction and wear tester, fix the cylindrical sample from step (2) laterally on the upper clamp of the friction and wear tester, and move the position of the grinding pair so that the upper clamp is below the grinding pair. (12) Move the lower clamp downward so that the TC6 titanium alloy wire coated with molybdenum disulfide comes into contact with the YG20 cemented carbide grinding pair. The contact time is 15s when the load is 800N. (13) Set the motion mode to linear motion, the load to 800N, the speed to 20mm / min, the stroke to 20mm, and the temperature to 400℃, and start the experiment; (14) After the test, the friction coefficient data were obtained.

[0028] (15) such as Figure 2 As shown, the friction coefficient is <0.18, the maximum friction coefficient is > the average friction coefficient from 6s to 60s, and the molybdenum disulfide coating on the 8mm diameter TC4 titanium alloy wire is wear-resistant.

[0029] Comparative Example The same sample as in Example 1 was selected, and experiments were conducted. (1) Take a TC4 titanium alloy wire with a diameter of 8 mm and a molybdenum disulfide coating with a film thickness of 9.5 μm, and test the wear resistance of its molybdenum disulfide coating using the following method.

[0030] (2) Select cemented carbide YG20 as the grinding pair. The dimensions after machining are 50mm×20mm×10mm, and the surface roughness Ra=0.05μm. Clean the surface of the grinding pair with acetone and dry it. (3) Cut the TC4 titanium alloy wire with a diameter of 8 mm coated with molybdenum disulfide into cylindrical specimens with a length of 10 mm. (4) Mount the grinding pair on the lower clamp of the friction and wear testing machine, fix the cylindrical sample from step (2) laterally on the upper clamp of the friction and wear testing machine, and move the position of the grinding pair so that the upper clamp is below the grinding pair. (5) Set the motion mode to linear motion, load to 500N, speed to 10mm / min, and stroke to 10mm; (6) Move the lower clamp downwards so that the TC4 titanium alloy wire coated with molybdenum disulfide comes into contact with the YG20 cemented carbide grinding pair and start the experiment immediately. (7) Coefficient of friction Figure 3 As shown, after 15 seconds, the coefficient of friction is greater than 0.2, indicating that the molybdenum disulfide coating on the titanium and titanium alloy wire used for fasteners has failed and is not wear-resistant; the maximum coefficient of friction is 0.401, which occurs at 55.59 seconds, not in the first 5% of the overall time period, which also proves that the coating is not wear-resistant.

[0031] In summary, the results of the above embodiments show that the method for evaluating the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires for fasteners, as described in this invention, not only provides the requirements and testing methods for sample preparation but also provides a method for evaluating wear resistance. The obtained data exhibits good uniformity and high accuracy. Compared to Comparative Example 1, it can obtain accurate friction coefficient data and correctly evaluate the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires for fasteners.

[0032] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the disclosure herein. This application is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the claims of this application.

Claims

1. A method for evaluating and determining the wear resistance of molybdenum disulfide coatings on titanium and titanium alloy wires, characterized in that, The steps are as follows: 1) Preparation of grinding pairs: Select the corresponding material according to the material of the extrusion molding die, process it to obtain blocks with regular dimensions, and ensure that the surface is clean, without defects or obvious scratches; 2) Fixing the grinding pair: Fix the grinding pair prepared in step 1) on the lower sample fixture of the friction and wear testing machine, and ensure that it cannot move; 3) Processing molybdenum disulfide coated samples: Cut the fasteners coated with molybdenum disulfide into cylinders with a length of 3~50mm using titanium and titanium alloy wire; 4) Fixing the molybdenum disulfide coated sample: Fix the sample from step 3) laterally on the upper clamp of the friction and wear testing machine, with the length direction being the contact direction; 5) Set the motion mode of the friction and wear test to linear motion; 6) Set the experimental parameters on the software of the friction and wear testing machine: load, speed, stroke, and temperature; 7) Move the upper clamp that holds the molybdenum disulfide coated sample downwards so that the fasteners coated with molybdenum disulfide are made of titanium and titanium alloy wire above the grinding pair fixed in step 2). 8) Set a load to bring the grinding pair into contact with the molybdenum disulfide coated sample and maintain the contact for more than 1 second; 9) Click the "Start Test" button on the friction and wear testing machine, wait for the experiment to finish, and obtain the corresponding data of friction coefficient and time; 10) When the coefficient of friction is greater than or equal to 0.2, the molybdenum disulfide coating of titanium and titanium alloy wire used in fasteners fails and does not have wear resistance; When the coefficient of friction is <0.2, the time point at which the maximum coefficient of friction occurs is in the first 5% of the overall time period, and the maximum coefficient of friction is greater than the average value of the coefficient of friction in the last 1% to 95% of the time period, the molybdenum disulfide coating of titanium and titanium alloy wire for fasteners has not failed and has wear resistance.

2. The method for evaluating and determining wear resistance according to claim 1, characterized in that: Linear friction and wear tests can be repeated 1 to 30 times at the same location.

3. The method for evaluating and determining wear resistance according to claim 2, characterized in that: The average friction coefficient of the first linear friction and wear test is less than or equal to the average friction coefficient of other repeated tests, and the molybdenum disulfide coating of titanium and titanium alloy wires for fasteners has wear resistance.

4. The method for evaluating and determining wear resistance according to claim 2, characterized in that: The maximum friction coefficient in the first linear friction and wear test is greater than or equal to the maximum friction coefficient in other repeated tests, and the molybdenum disulfide coating on the titanium and titanium alloy wires used in fasteners has wear resistance.

5. The method for evaluating and determining wear resistance according to claim 1, characterized in that: The grinding pair is made of cemented carbide or high-temperature alloy with a surface roughness of Ra=0.02~0.5μm. The grinding pair is a disc or a cuboid. The size of the disc-shaped grinding pair is φ(10~200)mm×(3~20)mm, and the size of the cuboid-shaped grinding pair is (10~200)mm×(10-60)mm×(3~20)mm.

6. The method for evaluating and determining wear resistance according to claim 1, characterized in that: The diameter of the titanium and titanium alloy wire used for the fasteners is 2~8mm, and the length-to-diameter ratio is 1~5.

7. The method for evaluating and determining wear resistance according to claim 1, characterized in that: The molybdenum disulfide coating thickness of the titanium and titanium alloy wires used in the fasteners is 5-20 μm.

8. The method for evaluating and determining wear resistance according to claim 1, characterized in that: The load range is 50N-1000N, the stroke is 5mm-30mm, the speed is 5mm / min-50mm / min, and the temperature range is room temperature to 800℃.

Citation Information

Patent Citations

  • Method for testing friction and wear life of diamond-like carbon film

    CN113984505A

  • Method for testing frictional wear performance of cylindrical side coating

    CN116183419A